2007
DOI: 10.1103/physrevd.75.076003
|View full text |Cite
|
Sign up to set email alerts
|

Infrared properties of propagators in Landau-gauge pure Yang-Mills theory at finite temperature

Abstract: The finite-temperature behavior of gluon and of Faddeev-Popov-ghost propagators is investigated for pure SU (2) Yang-Mills theory in Landau gauge. We present nonperturbative results, obtained using lattice simulations and Dyson-Schwinger equations. Possible limitations of these two approaches, such as finite-volume effects and truncation artifacts, are extensively discussed. Both methods suggest a very different temperature dependence for the magnetic sector when compared to the electric one. In particular, a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
265
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(291 citation statements)
references
References 85 publications
26
265
0
Order By: Relevance
“…The momentum-space expressions for the transverse and longitudinal gluon propagators D T (p 2 ) and D L (p 2 ) can be found e.g. in [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The momentum-space expressions for the transverse and longitudinal gluon propagators D T (p 2 ) and D L (p 2 ) can be found e.g. in [3].…”
Section: Resultsmentioning
confidence: 99%
“…Lattice studies of the Landau-gauge gluon propagator around the deconfinement phase transition in pure SU(2) and SU(3) theory, as well as considering dynamical quarks, have been presented in [3][4][5][6][7][8][9][10]. Our SU(2) study has been reported in [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…A number of authors have used the GZ action to extend our knowledge about finite-temperature Yang-Mills further into the non-perturbative regime [20][21][22]. Our perspective in light of the altered GZ action is that it is convenient to use Coulomb gauge.…”
Section: Applications For Finite Temperaturementioning
confidence: 99%
“…They can be dealt with, for example, by using explicit additional renormalization conditions [31]. Calculations of the propagators can be found, e.g., in [31][32][33][34]. Here I aim at the calculation of three-point functions.…”
Section: Non-vanishing Temperaturementioning
confidence: 99%